Cultural Transformation in the Implementation of Integrated Quality Management in Islamic Education: : A Case Study at Minhaj Shahabah Islamic Boarding School Bogor - Abas Mansur Tamam; Suherman Suherman (Publikasi Indonesia, 2024)
This research discusses cultural transformation in the implementation of Integrated Quality Management (IQM) in Islamic education through a case study at the Minhaj Shahabah Islamic Boarding School in Bogor. The main objective of this research is to analyze how cultural transformation plays a role in the application of IQM in the Islamic education environment. The research employs a qualitative approach with data collection techniques involving observation, interviews, and document analysis. The results indicate that cultural transformation plays a key role in the successful implementation of IQM at the boarding school. Through a strong cultural shift, such as the incorporation of the values of the Al Qur'an and Sunnah as well as advice from Ulama, the boarding school creates a holistic and high-quality educational environment.